Money and banking : select research papers by the economists of Reserve Bank of India - Vasudevan, A., 1940-; Reserve Bank of India (New Delhi : Academic Foundation, 2003)
The Reserve Bank of India has promoted research right from the early years of its existence. This work includes research papers that have been prepared by some of the economists of the Bank.
Includes bibliographical references.
aug 05/06/13; oif 29/07/15; 28/08/15
Loans
Keywords: Money supply -- India; Monetary policy -- India; Banks and banking -- India